Chest CT in COVID-19 patients: Structured vs conventional reporting. Issue 138 (May 2021) - Stanzione, Arnaldo; Ponsiglione, Andrea; Cuocolo, Renato; Rumolo, Mariateresa; Santarsiere, Marika; Scotto, Riccardo; Viceconte, Giulio; Imbriaco, Massimo; Maurea, Simone; Camera, Luigi; Gentile, Ivan; Brunetti, Arturo
Highlights: Chest CT in COVID-19 is a crucial element for patient management. Radiology reports should convey CT data clearly and comprehensively. Conventional reports show heterogeneous quality. Structured reports meet the preferences of referring physicians. Abstract: Purpose: To assess clinician satisfaction with structured (SR) and conventional (CR) radiological reports for chest CT exams in coronavirus disease 2019 (COVID-19) patients, objectively comparing both reporting strategies. Method: We retrospectively included 68 CTs (61 patients) with COVID-19. CRs were collected from the digital database while corresponding SRs were written by an expert radiologist, including a sign checklist, severity score index and final impressions. New CRs were prepared for a random subset (n = 10) of cases, to allow comparisons in reporting time and word count. CRs were analyzed to record severity score and final impressions inclusion. A random subset of 40 paired CRs and SRs was evaluated by two clinicians to assess, using a Likert scale, readability, comprehensiveness, comprehensibility, conciseness, clinical impact, and overall quality. Results: Overall, 19/68 (28 %) and 9/68 (13 %) of CRs included final impressions and severity score, respectively. SR writing required significantly ( p < 0.001) less time (mean = 308 s; SD ± 60 s) compared to CRs (mean = 458 s; SD ± 72 s). On the other hand, word count was not significantly different ( p = 0.059, median = 100 and 106, range = 106–139 and 88–131 for SRs and CRs, respectively). Both clinicians expressed significantly (all p < 0.01) higher scores for SRs compared to CRs in all categories. Conclusions: Our study supports the use of chest CT SRs in COVID-19 patients to improve referring physician satisfaction, optimizing reporting time and provide a greater amount and quality of information within the report.